PENGARUH PROMOSI KESEHATAN MOBILISASI DINI TERHADAP PELAKSANAAN MOBILISASI DINI PADA IBU POSTPARTUM SC DI RSPB PEKANBARU - Ratmiwasi, Cici; Utami, Sri; Agritubella, Syafrisar Meri (Jurnal Endurance, 2017)
Early mobilization in the mother sectio caesarea is minimal movement of women done after aware of the influence of anasthesia is done in accordance with the needs and physical condition. There are several factors that influence a personâs attitude on of which is the level of knowlegde, level of knowledge of mothers about early mobilization can be obtained through health an effect of health promotion on early mobilization towards the implementation of early mobilization in mothers with after chilbirth with sectiocaesarea in the Petala Bumi General Hospital. This research method quasy experiment with the design of on group pretest-postest. The Number of respondens 30 people with Quota Sampling methode. To measure the implementation of early mobilization using observation sheet. The analysis using T Test Dependent. The Results showed that there are effect of health promotion on early mobilization towards the implementation of early mobilization in mothers after childbirth with sectio caesarea.Â  Â